Risk factors for premature coronary artery disease and determinants of adverse outcomes after revascularization in patients ≤40 years old - Mukherjee, Debabrata; Hsu, Amy; Moliterno, David J; Lincoff, A.Michael; Goormastic, Marlene; Topol, Eric J (The American journal of cardiology, 2003)
Smoking is an important and modifiable risk factor associated with premature atherosclerosis and the need for coronary revascularization in young adult patients ≤40 years old. Although intermediate and long-term survival is better in young adult patients after percutaneous coronary intervention, co-morbidities such as low ejection fraction, previous myocardial infarction, and previous bypass surgery are important adverse prognostic determinants.